Bilateral subdural haematomata and lumbar pseudomeningocele due to a chronic leakage of liquor cerebrospinalis after a lumbar discectomy with the application of ADCON-L gel. Issue 7 (16th June 2005) - Kuhn, J; Hofmann, B; Knitelius, H O; Coenen, H H; Bewermeyer, H
Abstract : The anti-adhesion gel ADCON-L has been available since the end of the 1990s. During disc surgery it can be applied to the spinal nerve roots and the dura mater spinalis in order to inhibit fibroblast migration and thus avoid postoperative adhesions or excessive keloids, respectively. Due to the way ADCON-L works, inadvertent, intraoperational dural lesions may stay open much longer than usual because ADCON-L inhibits the natural healing process. Possible consequences are a chronic leakage of cerebrospinal fluid in combination with intracranial hypotension syndrome. We report on a patient who underwent lumbar disc surgery with application of ADCON-L gel. Postoperatively he suffered from acute headache, nausea, and vomiting. A lumbar pseudomeningocele was demonstrated on magnetic resonance imaging (MRI). Furthermore, cranial MRI revealed bilateral, chronic subdural haematomata which indicated intracranial hypotension syndrome or continuous leakage of cerebrospinal fluid at the lumbar site. With conservative treatment the problems were gradually reduced and eventually the subdural haematomata were no longer detected. The pseudomeningocele persisted over a 4 month period of observation. Because of the complications we found, the local application of ADCON-L during lumbar disc surgery should be critically evaluated.